PENGARUH KEPEDULIAN LINGKUNGAN DAN SIKAP TERHADAP MINAT BELI PRODUK HIJAU (Studi Kasus Pada Konsumen Produk Hijau di Kabupaten Rembang) - Ming Ming Lukiarti (Sekolah Tinggi Ilmu Ekonomi YPPI Rembang, 2019)
Consumers who are aware of ecological problems certainly have environmental concerns and a good attitude to preserve the environment so that it will be easier for the emergence of interest in buying a green product in the future and maintain a positive attitude. This research was conducted on consumers who have already bought green products in Rembang Regency. The method used to determine the sample is nonprobability sampling with purposive sampling technique, the number of samples used in this study were 100 respondents. Data collection is done through questionnaires, interviews and observations. The data processing technique used is using SPSS 21, the first step is to test the instrument from a questionnaire distributed by validity test, reliability test, multiple regression test and determination test. The results of the study indicate that: (1) Environmental awareness has a positive and significant effect on buying interest in green products; (2) Attitudes have a positive and significant effect on buying interest in green products; (3) Environmental awareness and attitude simultaneously have a positive and significant effect on interest in buying green products.